Nutritional Status, Hypertension, Proteinuria and Glycosuria amongst the Women of Rural Bangladesh (Ibrahim Medical College Journal, 2009)
Methods and materials - A rural community was purposively selected in Sreepur thana of which four villages were selected randomly. The total population of all age groups was 14,165 and the eligible reproductive aged females were 3,820 based on age between 15 and 45 years. Sample size was estimated at 573 (15%) of the eligible participants depending on the availability of time and logistic support. The study design was to use a questionnaire related to age, education, family income, housing and sanitation. Height (ht), weight (wt) and blood pressure (BP) were measured. Urine protein was estimated. Clinical examinations noted the presence of anemia, jaundice, edema, ring-worm, scabies, goiter, xerophthalmia and gum bleeding. Body mass index (BMI) was calculated to determine their obesity or wasting. Results - Overall, 501 volunteered and the response rate was 87.4%. Of these participants, 30.3% were illiterate. Almost all of them had supply of tube-well water and 68% had sanitary latrines. Their mean (±SD) age was 30.2 (±2.9)y, wt was 46 (±8.5)kg, ht was 149 (±5)cm and BMI was 20.5 (±3.5). The poor women had significantly lower BMI than the rich [20.0 (2.93) vs. 21.2 (4.1), (p